2019
DOI: 10.1111/bph.14701
|View full text |Cite
|
Sign up to set email alerts
|

Adrenoceptors—New roles for old players

Abstract: Linked Articles This article is part of a themed section on Adrenoceptors—New Roles for Old Players. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v176.14/issuetoc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Different comparative analyses showed that Amiodarone, despite interacting with the ANS centrally [49] and peripherally [50,51] did not affect HRV. On the other hand, Flecainide and Propafenone have vagolytic [52] and beta-blocking [53] properties, which could further modulate sympathetic and parasympathetic activity in the heart [54,55] decreasing all the parameters of HRV in the time domain and the frequency domain including the markers of vagal activity [56]. On the contrary, Oymatrine, compared to Propafenone, increases HRV [57].…”
Section: Emotional Dysegulation and Heart Rate Variabilitymentioning
confidence: 99%
“…Different comparative analyses showed that Amiodarone, despite interacting with the ANS centrally [49] and peripherally [50,51] did not affect HRV. On the other hand, Flecainide and Propafenone have vagolytic [52] and beta-blocking [53] properties, which could further modulate sympathetic and parasympathetic activity in the heart [54,55] decreasing all the parameters of HRV in the time domain and the frequency domain including the markers of vagal activity [56]. On the contrary, Oymatrine, compared to Propafenone, increases HRV [57].…”
Section: Emotional Dysegulation and Heart Rate Variabilitymentioning
confidence: 99%
“…Different reasons could explain the divergence between humans and rodents. While β3-adrenoceptors play a major role in rodent AT, adult humans have white AT in which β3-adrenoceptors are poorly expressed and play only a minor role in lipolysis [54,55]. In spite of this, our results suggest a relevant role for this subtype in the control of obesity, since the β3-, but not β1-nor β2-adrenoceptor expression in hAT, inversely correlates to body mass index.…”
Section: Discussionmentioning
confidence: 51%
“…Until now, pharmacological modulation of β-adrenoceptors, especially the β3 subtype, had been a promising strategy to the treatment of obesity, and considerable efforts had been made to develop β3-adrenoceptor agonists. Unfortunately, this approach has not yet been successful [53,54]. Different reasons could explain the divergence between humans and rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, pharmacological modulation of β‐adrenoceptors, especially the β3 subtype, had been a promising strategy to the treatment of obesity, and considerable efforts had been made to develop β3-adrenoceptor agonists but this approach has not yet been successful ( 54 , 55 ). However, while β3‐adrenoceptors play a major role in rodent AT, in adult human AT β3‐adrenoceptors are poorly expressed and play only a minor role in lipolysis ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%